Safety and patterns of survivorship in recurrent GBM following resection and surgically targeted radiation therapy: Results from a prospective trial. (2nd November 2022) - Smith, Kris; Nakaji, Peter; Thomas, Theresa; Pinnaduwage, Dilini; Wallstrom, Garrick; Choi, Mehee; Zabramski, Joseph; Chen, Clark; Brachman, David
Abstract: Background: Treatment of recurrent glioblastoma (GBM) remains problematic with survival after additional therapy typically less than 12 months. We prospectively evaluated whether outcomes might be improved with resection plus permanent implantation of a novel radiation device utilizing the gamma-emitting isotope Cs-131 embedded within bioresorbable collagen tiles. Methods: Recurrent histologic GBM were treated in a single-arm trial. Following radiation, the surgical bed was lined with the tiles. Subsequent treatments were at the treating physician's discretion. Results: 28 patients were treated (20 at first recurrence, range 1–3). Median age was 58 years, KPS was 80, female:male ratio was 10:18. Methylguanine methyltransferase (MGMT) was methylated in 11%, unmethylated in 18%, and unknown in 71%. Post implant, 17 patients (61%) received ≥ 1 course of systemic therapy. For all patients, Kaplan-Meier estimates of median time to local failure were 12.1 months, post-implant survival was 10.7 months for all patients and 15.1 months for patients who received systemic therapy; for all patients, median overall survival from diagnosis was 25.0 months (range 9.1–143.1). Sex, age, and number of prior progressions were not statistically significant. Local control was continuously maintained in 46% of patients. Two deaths within 30 days occurred, one from intracranial hemorrhage and one after persistent coma. Three symptomatic adverse events occurred: one wound infection requiring surgery and two late radiation brain injury, resolved non-surgically. Conclusion: This pre-commercial trial demonstrated acceptable safety and favorable post-treatment local control and survival. The device has received FDA clearance for use in newly diagnosed malignant and all recurrent intracranial neoplasms.